Additional Comments on Student Values and Their Implication for Accounting Education. - Brenner, Vincent C. (The Accounting Review, 1974)
Abstract Presents a reply to comments made on the article "Some Observations on Student Values and Their Implications for Accounting Education," by Vincent Brenner. Relationship between attitudes and values; Reason for the adoption of the measurement technique; Need for awareness on the difference in attitudes or values between accounting students and non-accounting majors